The Mini Alcohol Craving Experience Questionnaire: Development and Clinical Application. (26th December 2016) - Coates, Jason M.; Gullo, Matthew J.; Feeney, Gerald F.X.; Kavanagh, David J.; Young, Ross McD.; Dingle, Genevieve A.; May, Jon; Andrade, Jackie; Statham, Dixie J.; Connor, Jason P.
Abstract : Background: Standardized alcohol craving scales are rarely used outside of research environments despite recognized clinical utility. Scale length is a key barrier to more widespread application. A brief measure of alcohol craving is needed to improve research and treatment of alcohol use disorders (AUDs). Grounded in the Elaborated Intrusion Theory of Desire, the Alcohol Craving Experience (ACE) Questionnaire comprises two 11‐item self‐report scales that assess past‐week frequency and maximum strength of alcohol craving. This study aimed to create a brief version of the ACE while maintaining psychometric integrity and clinical utility. Methods: Patients attending a university hospital alcohol and drug outpatient service for the treatment of AUD completed the ACE as part of a questionnaire battery. Three patient samples were utilized: 519 patients with pretreatment and outcome data, 228 patients with pretreatment data, and 66 patients who completed the ACE at treatment sessions 1 and 2. Results: The Frequency scale of the ACE possessed greater clinical utility and predictive validity than the Strength scale. Revision of the Frequency measure produced a 5‐item "Mini Alcohol Craving Experience" (MACE) Questionnaire. Satisfactory validity (construct, predictive, concurrent, convergent, and incremental) and reliability (internal and test–retest) were maintained. A 1 standard deviation increase in pretreatment MACE score was associated with a 54 percentage increase in the odds of patient lapse or dropout. Conclusions: The MACE provides a brief, theoretically, and psychometrically robust measure of alcohol craving suitable for use with AUD populations in time‐limited clinical and research settings. Abstract : A brief version of the Alcohol Craving Experience (ACE) Questionnaire was developed for time‐limited settings. The five‐item Mini Alcohol Craving Experience (MACE) demonstrated satisfactory validity (construct, predictive, concurrent, convergent, and incremental) and reliability (internal and test–retest). A 1 standard deviation increase in pretreatment MACE score was associated with a 54% increase in the odds of patient lapse or dropout. The MACE is a brief, theoretically and psychometrically robust measure of alcohol craving suitable for time‐limited clinical and research settings.